Pertanggungjawaban Konsultan Pengawas Jasa Konstruksi Terhadap Tindak Pidana Korupsi - Irfan, Syahricky; Rambey, Guntur (Dinasti Research, 2024)
This study examines the liability of construction service supervisory consultants in criminal acts of corruption, with a focus on criminal law enforcement mechanisms, forms of liability, and recommendations for strengthening the supervision system and preventing corruption in the construction sector. Using normative legal research methods, this study examines primary, secondary, and tertiary legal materials relevant to the research topic.The approaches used include statute approach, conceptual approach, and case approach. The analysis is conducted qualitatively with descriptive analytical method to produce a comprehensive picture of the problem under study.The results show that the criminal law enforcement mechanism against supervisory consultants involved in corruption involves a complex process, from investigation to court decisions, with the main challenge being proving the involvement of consultants in corruption schemes. The form of liability of supervisory consultants can be in the form of individual, corporate, or in solidum criminal liability, with sanctions that include imprisonment, fines, and state loss recovery obligations.The research also produces recommendations for strengthening the supervision system and preventing corruption, which include the implementation of technology in project supervision, increasing transparency through e-procurement, strengthening the whistleblowing system, improving the quality and independence of supervisory consultants, as well as regulatory reform and law enforcement.The research conclusions emphasize the importance of a holistic approach in addressing corruption in the construction sector, incorporating legal, management, technological and ethical aspects. The implementation of the proposed recommendations is expected to contribute to the creation of a cleaner, more efficient, and higher quality construction industry in Indonesia.